John Boyne’s The Boy in Stripped Pyjamas: A Critique of Bare Life - Sharma, Pradip (Literary Studies, 2025)
Nailed to the starve and immolate policy hailed by the Nazi in the concentration camps, John Boyne’s novel, The Boy in Stripped Pyajamas rethinks the immured detainees’ bare lives that have lost socio-political entitlements. The study assesses precarious life of the indentured detainees which ironically implies their inclusion in the holocaust politics. The encamped Jews have lost their biỏs, qualified life which means they are consigned to hold zoẻ, a mere biological life that every living species shares. In addition, it examines their subjectification to killable body. Informed by Giorgio Agamben’s extension of Michel Foucault’s biopolitics especially the notion of homo sacer who is destined to hold the bare life after stripping down of his biỏs, the study probes into Jewish ripped off life in concentration camp surfaced in Boyne’s narrative. Agamben’s notion of biopolitics contours a critical insight to interrogate the politically hacked lives of the immured Jews in a normalized regime of Hitler in Boyne’s narrative. The study critically reads the abject bare life of the holocaust detainees focusing on their outlawed lives. It concludes that Boyne’s narrative constitutes a literary discourse to brood over how Nazi regime rips off detainees’ human position that helps to advocate the human rights of ordinary people